The 3rs concept as an added value for improving students’ green awareness through TVET green education in Malaysia / Sarsvathy Thirupathy and Ramlee Mustapha - Thirupathy, Sarsvathy; Mustapha, Ramlee (2023)
On a global scale, we are facing four major environmental crises ̶ environmental degradation, depletion of natural resources, waste management, and climate change. These crises are interrelated and connected to waste generation and waste management. Hence, waste generation and management is a global issue requiring special attention. Without green friendly solution, the world is facing a menacing future. Part of the feasible solution is to inculcate green values in the young generation through green TVET education. The 3Rs concept (Reuse, Reduce and Recycle) can be used to improve students’ green awareness, knowledge, and skills. In fact, the 3Rs is a sustainable approach to waste management that can assist in reducing pollution and greenhouse gas emissions. Green composting is a good practice by recycling organic waste to produce compost and biogas. It is an alternative option to open dumping, a major greenhouse gas emission source. This conceptual paper aims to investigate using the 3Rs concept as an added value for improving students’ green awareness through TVET green education in Malaysia. In the Malaysian junior high school curriculum, the elements of the 3Rs concept are taught in the Design and Technology (D&T) subject. However, evaluating its effectiveness in reducing environmental degradation is seldom being carried out. Thus, it is critical to investigate the effect of the 3Rs concept in enhancing green awareness among junior high school students in Malaysia.